New approach methodologies for in vitro toxicity screening of nanomaterial using a pulmonary three-dimensional floating extracellular matrix model - Soojin Kim; Mi-Sun Choi; Hyun Jegal; Min Beom Heo; Minjeong Kwak; Hyun Kyong Shon; Seungwoo Song; Tae Geol Lee; Ji-Ho Park; Dong Woo Lee; Seokjoo Yoon; Jung-Hwa Oh (Journal of Biological Engineering)
Abstract Background Nanomaterials offer increasing applications across diverse sectors, including food science, medicine, and electronics. Environmental risk assessment is crucial for ensuring the safety and sustainability of nanomaterials. However, high-throughput screening (HTS) of their potential toxicity remains challenging owing to their unique physicochemical properties. Results This study introduces a novel pulmonary three-dimensional (3D) floating extracellular matrix (ECM) model utilizing a 384-pillar/well platform for HTS of nanotoxicity. Compared with conventional HTS models based on two-dimensional (2D) cells, the 3D model developed in this study successfully addressed the issues related to the aggregation and sedimentation of nanoparticles and their possible optical interference with the toxicity assays. Using 20 nm silica nanoparticles (SiNPs), we assessed cell viability and nanoparticle uptake in both serum-containing and serum-free culture media. While the 2D model showed high SiNPs toxicity regardless of the media composition, the pulmonary 3D floating ECM model demonstrated variable toxicities that depended on the SiNPs behaviors under different conditions. Conclusions By reducing the uncertainties associated with the sedimentation and optical interference of nanomaterials, our 3D model provided a more precise analysis of cytotoxicity. This study highlights the potential of using new approach methodologies and improved HTS approaches to enhance the efficiency and accuracy of risk assessment protocols for emerging nanomaterials.